A new species of \(Platylomia\) Stål, 1870 (Hemiptera: Cicadidae) from Vietnam, with a key to species - Hoang Yen, Luu; Thai, Pham Hong; Constant, Jerome (Academia Journal of Biology, 2022)
One new species of the Platylomia radha species group, Platylomia minhi sp. nov., from Sapa, Hoang Lien National Park, Lao Cai province, north Vietnam is described. Synonymic lists for the five species of the Platylomia genus from Vietnam are provided. A key to five species of Platylomia genus: Platylomia bocki, Platylomia duffelsi, Platylomia malickyi, Platylomia operculata, and new species from Vietnam is provided. Photos of the adult, illustrations of the male genitalia, a distribution map of the new species are also given.